No synergistic effect of subtherapeutic doses of donepezil and EVP‐6124 in healthy elderly subjects in a scopolamine challenge model. Issue 1 (2nd April 2019) - Baakman, Anne Catrien; Alvarez‐Jimenez, Ricardo; Loewen, Gordon; de Kam, Marieke L.; Broekhuizen, Karen; Hilt, Dana C.; Groeneveld, Geert Jan
Abstract: Introduction: Donepezil is a widely used cholinesterase inhibitor in the management of Alzheimer's disease. Despite large‐scaled evidence for its efficacy, elevated peripheral ACh levels often lead to side effects and are dose limiting. The present exploratory study is designed to determine the potentiation of the effects of donepezil by cotreatment with EVP‐6124, an alpha‐7 nicotinic agonist, to reduce scopolamine‐induced cognitive deficits in healthy elderly subjects. Secondary objectives are to explore safety and pharmacokinetic and pharmacodynamics effects of EVP‐6124 alone and in combination with donepezil compared to placebo. Methods: A phase I randomized, single‐center, placebo‐controlled, double‐blind, five‐way, partial crossover study was performed with donepezil 2.5, 5 mg or placebo combined with EVP‐6124 0.3, 1, 2, 4 mg or placebo in three cohorts of healthy elderly subjects in a scopolamine (0.3 mg i.v.) challenge test. Safety, pharmacokinetic, and pharmacodynamics outcomes were assessed. Results: A total of 36 subjects completed the study. Donepezil pharmacokinetic parameters were similar with and without EVP‐6124. Effective dose combinations were donepezil/EVP‐6124(5/2 mg) and donepezil/EVP‐6124 (5/0.3 mg) and showed improvements of the delayed recall of the Visual Verbal Learning Test (1.2; CI = 0.1–2.3) and reaction time during the two‐back condition of the N‐back (−42; CI = −77, −8), respectively. Overall, no marked reversal of scopolamine effects was observed. Discussion: This study shows no synergistic effect of subtherapeutic doses of donepezil and EVP‐6124 in a scopolamine challenge model in healthy elderly subjects. Dosing of scopolamine and the combination of donepezil and EVP‐6124 requires further study.